Comparison of Serum LP-PLA2 Level and some Nutritional Factors between Well-Controlled and Poorly-Controlled Diabetic Patients - Ali Cheraghi; Maryam Mahmoudi; Korosh Jafarian; Mohammadreza Eshraghian; Sanaz Soltani; Mahnaz Zarei; Farjam Godarzi; Yas Kalikias; Mahmoud Jalali (Acta Medica Iranica, 2015)
Lipoprotein-associated phospholipase A2 (Lp-PLA2) is produced by inflammatory cells, bound to LDL and other lipoproteins, and hydrolyzes oxidized phospholipids in LDL. Type 2 diabetes is the most common form of diabetes some investigations show the association of lipoprotein-associated phospholipase A2 mass and activity with the incidence of cardiovascular disease (CVD) in populations with high prevalences of insulin resistance and diabetes. This study is a cross-sectional descriptive and analytic study on 80 individuals with diabetes referring to the Tehran Diabetes Association. Patients divided into two groups (well-controlled and poorly controlled) based on their HbA1C. Personal information, anthropometric assessments (including height, weight, waist circumference and hip circumference) and semi-quantitative 147 items FFQ was used and vein blood samples were taken. After plasma separation, blood sample used for FBS, HbA1c and LP-PLA2 measurement. The independent sample T test was used for comparing means. Data analyses showed a significant difference between weight and WHR (waist to hip ratio) means in two studied groups, also there was a statistically significant difference in food intake (Energy, carbohydrate, protein, micronutrients percent and some of the micronutrients). FBS, HbA1C and LP-PLA2 means showed statistically significant difference (P<0/001) between two groups. This study showed LP-PLA2 is elevated in poorly-controlled patients compared to well-controlled diabetic patients, which may suggest some nutritional factors contributing to the regulation of this enzyme.